SBM ITB Curriculum Enhancement Proposal in The Face of Business School Competition in South East Asia - Setiawan, Rully; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2013)
The interesting phenomenon occurs nowadays with intense competition among business and management schools in Indonesia and the South East Asia region. Business schools would play a major role in the near and long term future as one of the most important part in the development of Indonesian economy. And it would be wise that the future generation will be leading the pivotal positions in the domestic and multinational business companies that held their presence in Indonesian soil rather than maintaining foreign labors dependencies in vital positions. The thesis research was conducted at SBM ITB Bandung Undergraduate Program and by benchmarking it with several top business and management school in South East Asia region. External and internal analysis revealed the problem root cause that SBM ITB is facing. The external factors pictured the detailed information of the business and management program that SBM ITB and its competitors is currently running. The internal factors showed what SBM ITB is currently lacks against its competitors. The solutions to answer the problem root cause at SBM ITB are constructed carefully by managing integration between the current strength of learning methods at SBM ITB and the business solutions alternatives proposed by the research. The alternatives offered ranging from offering additional courses solution to the existing curriculum, suggesting an increased number in academic staffs and by increasing the efforts in communicating the improvement that is being made at SBM ITB. In the end it is crucial to set the goal for SBM ITB to both attract the qualified prospective students and produce bachelor graduates in business and management program that have the same qualification with its international competitors. Therefore SBM ITB graduates can compete in the business field of national and international level and by default it is also lifting the reputation of SBM ITB.Â Keyword : Business, Course, Curriculum, Management, School